Management of Chronic Tinnitus and Insomnia with Repetitive Transcranial Magnetic Stimulation and Cognitive Behavioral Therapy – a Combined Approach - Richter, Kneginja; Acker, Jens; Miloseva, Lence; Peter, Lukas; Niklewski, Günter (Frontiers in Psychology, 2017)
It has been estimated that up to 80% of people will experience symptoms of tinnitus over the courses of their lives, with rates of comorbid sleeping problems ranging from 50% to 77%. Because of a potential connection between tinnitus and sleep disorders as well as high rates of comorbid psychiatric disorders, interdisciplinary approaches to treatment seem to be the most efficient option. In this study, we present the case of a 53-year-old male patient, who started to experience symptoms of tinnitus at the age of 49, most likely caused by work-related stress. Over the course of his illness, the patient developed comorbid insomnia. He consulted us for treatment of both conditions and we developed a treatment plan with ten sessions of repetitive transcranial magnetic stimulation (rTMS) followed by ten sessions of cognitive behavioral therapy (CBT). We used the Tinnitus Fragebogen (TF) to assess the severity of the tinnitus, the Beck Depression Inventory (BDI-II) for depressive symptoms, and the WHO Well-being Index (WHO-5) for subjective well-being. Improvements could be achieved with regard to both diagnoses and the patient went from severe (48) to clinically negligible (12) TF scores, from minimal (BDI-II score 10) to no (0) depressive symptoms, and from just above critical (WHO-5 percentile 52) to above average (84) well-being. The combination of technological and psychological approaches to treat tinnitus and insomnia thus proved successful in this case. One may therefore conclude that rTMS may be considered an effective first therapeutic step for tinnitus treatment prior to CBT. To our knowledge this is the first published case in which rTMS and CBT were combined for tinnitus therapy. The approach proved successful since it led to a considerable increase in well-being and everyday functioning. To gauge the effect on a more general level, large-scale studies are still needed to cancel out potential placebo effects. Likewise, the importance of the order of the two treatments, and the possibility of using other therapies in combination with CBT to address certain tinnitus subtypes and different etiologies must be studied in greater detail.